THE PHENOMENON OF FAJR ATTACKS IN THE ELECTIONS: AN ANALYSIS OF HASBI ASH-SHIDIEQY’S INTERPRETATION OF Q.S. AL-BAQARAH VERSE 188 - Safitri, Fazida (Sekolah Tinggi Agama Islam Sadra, 2024)
This research focuses on the phenomenon of fajr raids in elections analyzed using Hasbi Ash-Shidieqy’s interpretation of Q.S. Al-Baqarah [2]: 188. As a country with a democratic political system, Indonesia holds a democratic party called elections every 5 years to elect representatives of the people. The People’s democratic party, which is expected to give birth to honest leaders who are free from corruption, collusion, and nepotism, instead brings new corrupt seeds. This is based on the election system that has been corrupted by money politics. All means are used by prospective leaders to smooth their way to winning the election. Candidates distribute money to the public to buy people’s votes covered with the word alms. The purpose of this study is to identify the relationship between the phenomenon of fajr raids that often occur before elections with Q.S. Al-Baqarah [2]: 188. The method used in this research is descriptive-qualitative by using literature review. The results of this study indicate that the narrative of the Qur’anic text in Q.S. Al-Baqarah [2]: 188 indicates the prohibition of taking and controlling other people’s property in a way that is not justified by shara, including the practice of fajr attacks in elections because it is classified as rashwah. The gift is not based on sincerity because they expect the public to vote for the one who gave the fajr attack.